Molecular communications techniques for the internet of bio-nano things - Figueiredo, Sofia Alexandra Duarte (2021)
The ”Internet of Bio-Nano Things” (IoBNT) is a new networking paradigm defined as the interconnection of nanoscale devices. IoBNT is a revolutionizing concept that will likely enable a wide range of applications, in particular, it is envisioned that healthcare systems will be transformed with the development and integration of body-centric networks into future generations of communication systems. Within this context, molecular communications (MC) emerge as the most promising way of transmitting information for in-body communications, due to being inherently biocompatible, energy-efficient, and robust in physiological conditions. One of the biggest challenges is how to minimize the effects of environmental noise and reduce intersymbol interference (ISI) which can be very high in an MC via diffusion scenario. Analogous to traditional communications, channel coding is one of the most promising types of techniques for addressing this problem. This work is based on the study and evaluation of novel energy efficient and low complexity coding, modulation and detection schemes for MC. With a special focus on the implementation of Tomlinson, Cercas, Hughes (TCH) codes as a new attractive approach for the MC environment, due to the particular codeword properties which enable simplified detection. Simulation results show that TCH codes are more effective for these scenarios when compared to other existing alternatives, without introducing too much complexity or processing power into the system. Furthermore, an experimental macroscale proof-of-concept is described, which uses pH as the information carrier and demonstrates that the proposed TCH codes can improve the reliability in this type of communication channel.